Electromagnetic induction measurements with the vertically oriented dipole of the CMD Mini Explorer (118 cm transmitter-receiver spacing) taken in the Ahr floodplain at Mayschoß, Rhineland-Palatinate (Germany) - Marco Pohle; Matteo Bauckholt; Ulrike Werban (PANGAEA, 2025)
Electromagnetic induction (EMI) was measured with a CMD-Mini Explorer and a CMD Explorer (both GF Instruments s.r.o., Brno, Czech Republic) in June 2022. We used the vertical dipole (VDP) at coil spacings of 0.32 m (VDP1, CMD Mini Explorer), 0.71 m (VDP2, CMD Mini Explorer), 1.18 m (VDP3, CMD Mini Explorer), 1.48 m (VDP4, CMD Explorer), 2.82 m (VDP5, CMD Explorer) and 4.49 m (VDP6, CMD Explorer). With the existing coil spacings, effective penetration depths of 0.5 m (VDP1), 1.0 m (VDP2) and 1.8 m (VDP3) for the CMD Mini Explorer and 2.2 m (VDP4), 4.2 m (VDP5) and 6.7 m (VDP6) for the CMD Explorer could be achieved. According to the manufacturer, 70 % of the signal originate from above these depths. The EMI sensors measured the apparent electrical conductivity (ECa, in mS/m). Measurements were taken by carrying the instrument about 0.2 m (CMD Mini Explorer) respectively 0.9 m (CMD Explorer) above the ground while being directly connected to Differential -GPS (Leica GPS1200) for positioning. The acquisition rate was five measurements per second. Data quality was checked by measuring a reference line before and after each measurement. The maximum offset of the EMI values between the two time points was 1.2 mS/m. A correction of the data was not necessary. We removed the reference lines and single outliers. In addition, two interference areas were removed from all EMI data sets. (1) a L-shapped area, running from north to the center and then to east, in which an underground power cable runs. (2) an area on the north-eastern part of the measurement area. Information on the location and extent of the removed interference areas can be found in the enclosed explanation of the EMI measurements. The data set contains the EMI data with an intercoil spacing of 1.18 m (VDP3, CMD Mini Explorer).
In: Pohle, M et al. (2025): Near surface geophysical data (Electromagnetic Induction and Electrical Resistivity Tomography) from the Ahr floodplain at Mayschoß, Germany [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.974990